THE EFFECT OF TMD ON THE PERIODS AND MODE SHAPES OF THE REINFORCED CONCRETE BUILDING BY FINITE ELEMENT ANALYSIS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Earthquake engineers have taken many precautions in their building designs to protect and minimize destructive effects. In this way, many new design and reinforcement methods have been developed against seismic loads. The use of a tuned mass damper (TMD) is one of the developed methods. One of the most important negative aspects of the use of TMD is the increase in the structural period. Therefore, in this study, the effects of TMD on periods and mode shapes in simeterically reinforced concrete building model were investigated. For this, two models with and without TMD were created by the finite element method and modal parameters were compared. As a result of the data obtained, it has been observed that the building model makes more balanced displacements, as can be understood from the mode shapes, without increasing the period of the building to a dangerous level. It is known that TMD reduces the seismic effect by acting in the opposite direction to the seismic effect on the structure. Tuned mass damper can be used in structures, provided that it does not increase the structure period too much.